(untitled) (Revista ABRA, 2019)
The water closets, daily and indispensable places, are the scene of a homosexual practice called cruising that challenges the heterosexual policy materialized in rules that regulate the building and legitimize, simultaneously, the binary construction of the genre associated with genitality. As a result of a doctoral seminar, the present essay shows the results of an investigation that includes the main nomothetic Costa Rican guidelines that protect the design and construction of bathrooms. Likewise, testimonies of men are collected, and they, in order to face the heteronormative praxis and rhetoric, proceed to appropriate these spaces to subvert their connotation and, thus, dismantle their function as a deponent of the genre.